2023
DOI: 10.2196/49771
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of ChatGPT 3.5 and 4.0 as a Source of COVID-19 Information: Comprehensive Comparative Analysis of Generative and Authoritative Information

Guoyong Wang,
Kai Gao,
Qianyang Liu
et al.

Abstract: Background The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has necessitated reliable and authoritative information for public guidance. The World Health Organization (WHO) has been a primary source of such information, disseminating it through a question and answer format on its official website. Concurrently, ChatGPT 3.5 and 4.0, a deep learning-based natural language generation system, has shown potential in generating diverse text types based on user input. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…ChatGPT was able to gather, review, and generate credible text relevant to public health and allied content. In another study, Wang et al ( 37 ) estimated the accuracy of COVID-19 information by ChatGPT 3.5 and 4.0. The authors found that ChatGPT 3.5 and 4.0 can produce correct and appropriate COVID-19 information to a certain extent, but compared to global health organizations’ responses, gaps and deficiencies exist.…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT was able to gather, review, and generate credible text relevant to public health and allied content. In another study, Wang et al ( 37 ) estimated the accuracy of COVID-19 information by ChatGPT 3.5 and 4.0. The authors found that ChatGPT 3.5 and 4.0 can produce correct and appropriate COVID-19 information to a certain extent, but compared to global health organizations’ responses, gaps and deficiencies exist.…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting observations we encountered while working with the chatbots was the variation between the chatbots 1 and 2. Both chatbot 1 and chatbot 2 were trained with data extending until September 2021, but chatbot 2 is considered the more advanced version and in our experience, had more independent thinking . When asking the chatbots to generate text, we used the same online session to provide consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Both chatbot 1 and chatbot 2 were trained with data extending until September 2021, but chatbot 2 is considered the more advanced version 80 and in our experience, had more independent thinking. 81 When asking the chatbots to generate text, we used the same online session to provide consistency. Chatbot 1 was compliant and completed the tasks without needing redirection, but chatbot 2 had difficulty complying, required restarting new sessions, retraining each one, and several reminders of the prompt to finish writing all 10 abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…One example is generative AI technologies, such as large language models [10][11][12]. The presence of AI, such as ChatGPT, has revolutionized how we process information, communicate, and learn [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Generative AI as Virtual Healthcare Assistant for Enhancing Patient Care Quality ChatGPT, as a highly advanced virtual assistant, can assist in various contexts [14], including the healthcare sector [16]. It has been challenging for the healthcare sector to deliver effective, efficient, and high-quality patient care [17].…”
Section: Introductionmentioning
confidence: 99%